Konsep Pendidikan Akhlak dalam Al-Qur’an: Kajian Tafsir Surat Al-Baqarah ayat 83 - Sudarto, Sudarto; Noviani, Dwi; Muttaqien, Muhammad Amin (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Moral problems are lifelong problems of human presence on earth. History tells us that not a few civilizations collapsed due to moral deterioration. In Islamic studies, a separate terminology is found when faced with the discussion of morality, namely “akhlaq” which in some literature is also equated with personality or character. Apart from the exact equivalent of the word "akhlaq", as a plenary religion Islam offers the concept of the formation of noble morals, one of which is as stated in verse 83 of Surah al-Baqarah. This paper is prepared based on qualitative data obtained through document study activities. These documents are obtained through various sources. Most quotes, regardless of opinions, are displayed without interpretation. Surah al-Baqarah verse 83 introduces the dimensions of spirituality, religiosity, individual and social values. In the context of Qur'an-based moral education, the verse can be used as a guideline for learning and teaching activities. This article is not proposed as a form of problem solving, but rather is intended as additional literature for a more comprehensive review.